2006
DOI: 10.1590/s1519-566x2006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da temperatura e cama do aviário na virulência de Beauveria bassiana (Bals.) Vuill. e Metarhizium anisopliae (Metsch.) para o controle do cascudinho (Alphitobius diaperinus) (Panzer) (Coleoptera: Tenebrionidae)

Abstract: Bolsista de Produtividade em Pesquisa/CNPqNeotropical Entomology 35(1): 075-082 (2006) Effect of Temperature and Poultry Litter in Beauveria bassiana (Bals.) Vuill. and Metarhizium anisopliae (Metsch) Virulence against the Lesser Mealworm Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae)ABSTRACT -This study was carried out to evaluate the influence of temperature and poultry litter on germination vegetative growth virulence and conidial production of Beauveria bassiana (Bals.) Vuill. and Metarhizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
0
16
0
4
Order By: Relevance
“…Besides, the homoeothermic immune system is complex and efficient, hindering fungi growth. Inglis et al (1999) claimed that this fungus was very sensitive to variable temperatures, and Alexandre et al (2006) verified that at 32ºC, the germination of B. bassiana was totally inhibited. CV treatment (%) = 12,24 CV time (%) = 11,37 CV weight gain (%) = 12,39…”
Section: Bird Evaluationmentioning
confidence: 92%
“…Besides, the homoeothermic immune system is complex and efficient, hindering fungi growth. Inglis et al (1999) claimed that this fungus was very sensitive to variable temperatures, and Alexandre et al (2006) verified that at 32ºC, the germination of B. bassiana was totally inhibited. CV treatment (%) = 12,24 CV time (%) = 11,37 CV weight gain (%) = 12,39…”
Section: Bird Evaluationmentioning
confidence: 92%
“…This entomopathogenic fungus occurs naturally in poultry houses (Steinkraus et al, 1991;Alves et al, 2005) and presents great potential for pest control (Oliveira et al, 2014). Moreover, this fungus has been shown to be effective both under laboratory conditions (Alexandre et al, 2006;Rohde et al, 2006;Alves et al, 2008) and in field assays (Alves et al, in press).…”
Section: Laboratory and Field Evaluation Of A Cypermethrinbased Insecmentioning
confidence: 99%
“…Rohde et al (2006) tested more than 100 isolates of B. bassiana and M. anisopliae against lesser mealworms and reported that the isolate Unioeste 04 presented high killing efficiency and excellent production characteristics. Alexandre et al (2006) evaluated the effect of environmental temperature and litter type on the germination, vegetative growth, virulence, and production of conidia of B. bassiana and M. anisopliae isolates. The authors found that high environmental temperature (32ºC) and used litter influenced fungi virulence and other parameters, especially of B. bassiana isolates.…”
Section: Advances and Perspectives Of The Use Of The Entomopathogenicmentioning
confidence: 99%
“…Another important finding of that study was that the longer the contact of insects with the substrates (new and reused litter and soil), the lower the mortality. Santoro et al (2008) selected B. bassiana isolates and evaluated their lethal concentrations for the control of the lesser mealworm, and determined a LC50 of 8×105 conidia/mL for the isolate Unioeste 04, which was selected by Rohde et al (2006) and used in the studies of Alexandre et al (2006), Haas-Costa & Alves (2007), and Alves et al (2008).…”
Section: Advances and Perspectives Of The Use Of The Entomopathogenicmentioning
confidence: 99%